2-Cyano-3-(2,3,6,7-tetrahydro-1H,5H-benzo[ij]quinolizin-9-yl)prop-2-enoic acid dimethyl sulfoxide monosolvate - Yennawar, Hemant (International Union of Crystallography, 2012)
In dimethyl sulfoxide solvated 9-(2-carboxy-2-cyanovinyl)julolidine, C(16)H(16)N(2)O(2)·C(2)H(6)OS, the essentially planar –CH=(CN)–CO(2)H substituent (r.m.s. deviation = 0.014 Å) is almost coplanar with respect to the benzene ring, the dihedral angle between the two planes being 0.48 (2)°. The conformations of the fused, non-aromatic rings were found to be half-chair. In the crystal, the acid molecule forms a hydrogen bond to the O atom of the solvent molecule. The acid molecule is disordered over two positions with respect to the methylene C atoms in a 1:1 ratio. The crystal studied was found to be a racemic twin.